The Influence of Service Quality, Price, and Location on Purchasing Decisions at Cafe Fameliza Baron Nganjuk - Aditya, Bima; Sumantri, Bambang Agus (Universitas Nusantara PGRI Kediri, 2024)
Research aim : The purpose of this study is to determine and analyze the effect of service quality, price, and location on purchasing decisions at café fameliza Baron Nganjuk. Design / Method / Approach : This study uses a quantitative approach method with a type of causality. The population in this study is all consumers of café fameliza Baron Nganjuk whose number is infinite or uncounted. The sample used in the study was 40 respondents taken using accidental sampling technique . Data collection techniques using questionnaires. Data analysis of this study used multiple linear regression method. Research Finding: The results showed that the quality of service, price and location had a significant effect on purchasing decisions at café fameliza Baron Nganjuk. Theoretical contribution/originality: lies in a deep understanding of how service quality, price, and location together influence a consumer's purchasing decision-making process. This research explores the complex dynamics between these three factors and how the interactions between them can shape consumer preferences as well as influence purchasing behavior Practitionel/Policy implication: This study provides practical implications for Café Fameliza Baron Nganjuk in improving purchasing decisions Research limitation: The limitation of this study is that it spends too much time in sampling because it has entered the rainy season.